Improvements in Primary Emergency Care Understanding during Matches for Football Coaches and Referees in East Java - Gunawan, Erik Jaya; Arisanti, RR Shinta; Yuwono, Natalia; Suisan, Yohan Christian; Sasono, Bimo (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Improper initial management of emergency conditions during football matches causes long-term morbidity, affects the athlete’s future performance, and may be life-threatening. Football coaches and referees may come from non-medical backgrounds, but they should understand how to provide primary care in emergency situations during matches. This program aims to improve the primary emergency care understanding of the coaches and referees in East Java. The program was conducted in September 2022 – January 2023. All referees, assistant referees, and coaches of the Football Association of the Indonesia (FAI) region East Java (128 participants) were included. The primary emergency care training material consisted of video, PowerPoint media, and hands-on mannequins. Participants were given pre-and post-test to assess their level of knowledge, with a passing grade 75. Comparative tests (Wilcoxon signed rank, McNemar, and Chi-square test) were used to analyze the data. The median of the pre-and post-test scores were 62.5 and 87.5. There was a significant difference between pre-and post-test scores (p < 0.001). There was no significant difference between coaches and referee groups in pre-test scores (p = 0.743). This program improved the primary emergency care understanding during matches of coaches and referees.